Home » Aptitude » Algebra » Question
  1. If
    a + b − c
    =
    b + c − a
    =
    c + a − b
    and a + b + c ≠ 0, then
    a + bb + cc + a
    1. a ≠ b ≠ c
    2. a = b = c
    3. a = b ≠ c
    4. a ≠ b = c
Correct Option: B

a + b − c
=
b + c − a
=
c + a − b
a + bb + cc + a

⇒ 
a + b
c
=
b + c
a
=
c + a
b
a + ba + bb + cb + cc + ac + a

⇒  1 −
c
= 1 −
a
= 1 −
b
a + b b + c c + a

⇒ 
c
=
a
=
b
a + b b + c c + a

⇒ 
a + b
=
b + c
=
c + a
cab

⇒ 
a + b
+ 1 =
b + c
+ 1 =
c + a
+ 1
cab

⇒ 
a + b + c
=
b + c + a
=
c + a + b
cab

⇒ 
1
=
1
=
1
⇒ a = b = c
cab



Your comments will be displayed only after manual approval.